(untitled) (Applied Biological Research, 2023)
The present study focused on the antiproliferative effect ofmethanolicextractsofUlvapaschim(MEUP) on lung cancer cell lines A549 and H1299. The superoxide dismutase, catalase and glutathione reductase activities in MEUP wereassayed.Thintracellular reactive oxygen species, antioxidant potential, mitochondrial membrane potential and cell proliferation ability were also determineusing standard methods while the extracts were analysed by GCMS. The study showed that MEUP had selective antiproliferative effect on cancer cell lines with IC50 0.187 ± 0.120 µg µL-1for A549 and 0.130 ± 0.031 µg µL-1for H1299 cells as determined by 3-(4,5-dimethylthiazol-2-cyl)-2,5-diphenyltetrazolium bromide (MTT) assay. MEUP induced oxidative stress in dose-dependent manner as measured by dihydro-ethidium (DHE) and 2′,7′-dichloro-dihydro fluorescein diacetate (H2DCFDA) assays. Due to the induced oxidative stress by MEUP treatment, a rise in intracellular levels of antioxidant enzymes (glutathione reductase, superoxide dismutase, and catalase) was observed. A dose-dependent depolarization of mitochondrial membrane potential by 38% for A549 and 41% for H1299 cell lines was observed. The 2,2-diphenyl-1- picrylhydrazyl (DPPH) radical scavenging activity was 61.69% as compared to the ascorbic acid with EC50 of 176.7 ± 0.09 µg mL-1. GC-MS analysis of MEUP showed the presence of 1-dodecanol, 5-eicosene, neophytadiene, stearic acid, lauric acid, hexadecanoic acid, margaric acid, linoleic acid, L-α-terpineol, oleic acid, 9-octadecenamide, myristic acid and phytol known for their anticancerous properties. The phytochemical profile was evaluated for potential for serving as novel anticancer drug candidates.